Leveraging Technology to Engage Parents at Scale: Evidence from a Randomized Controlled Trial - Peter Leopold S. Bergman; Eric W. Chan (Center for Economic Studies and ifo Institute (CESifo), 2017)
While leveraging parents has the potential to increase student performance, programs that do so are often costly to implement or they target younger children. We partner text-messaging technology with school information systems to automate the gathering and provision of information to parents at scale. In a field experiment across 22 middle and high schools, we used this technology to send automated text-message alerts to parents about their child's missed assignments, grades and class absences. We pre-specified five primary outcomes. The intervention reduces course failures by 38% and increases class attendance by 17%. Students are more likely to be retained in the district. The positive effects are particularly large for students with below-average GPA and students in high school. There are no effects on standardized test scores however. We randomly chose either the mother or the father to receive the alerts, but there were no differential effects across these subgroups. As in previous research, the intervention appears to change parents' beliefs about their child's performance and increases parent monitoring. Our results show that this type of automated technology can improve student effort relatively cheaply and at scale.
Keywords: I20; I21; I24; I28; 330; education; information; experiments